REPUTASI DALAM KERANGKA KERJA PUBLIC RELATION - - Trimanah (Program Studi Ilmu Komunikasi FBIK Unissula, 2012)
Reputation is an important concept for the organization or company. In this fast-paced era of communication, the reputation is being one of the deciding factors in an effort to improve and maintain the company existantion. For that, the reputation should be managed well by creating an appropriate and strategic communications. Reputation is not the same as the image, also not the same as a brand. The process of building, maintaining and improving the reputation longer than the build, maintain and improve the image and brand. Therefore reputation is more established and stable than the image and brand. Image is formed based on the knowledge and information that received by a person. Communication does not directly lead to a certain behavior, but it is likely to affect the way we organize our picture of the environment. While brand is formed by communication messages, the actions of employees, customers, prospects and others, are defined by experience and perception clearly identify what makes an organization / product to be different. Identity will be attached to the brand image and then together to form theorganization's reputation in the public. Therefore between identity, image and brand will be linked to each other, which requires special handling and a clear public relations strategy, andin the end will bring a positive organizational reputation.Kata kunci: image, brand, identitas perusahaan, strategi Public Relations